Contactul româno-slav: efecte convergente în sintaxa românei vechi și a istroromânei (Romanian Studies Today, 2024)
In this paper I present two cases of Romance-Slavic contact: direct contact in bilingual context (Istro-Romanian and Croatian), and indirect contact via translations (old Romanian and Old Church Slavonic). After briefly presenting the syntactic features attested in Istro-Romanian and in old Romanian (but which have disappeared from modernRomanian), I focus on two features: the prenominal position of relational adjectives and auxiliary inversion, features explained by convergence (as they are attested both in Latin/ Old Romance and in the Slavonic contact languages, Croatian and Old Church Slavonic).  Finally, I make some theoretical remarks on the consequences of contact in syntax.
Keywords: old Romanian; Istro-Romanian; direct contact; written contact; convergence